Thermoplastics and thermoplastic composites - Biron, Michel (PDL handbook series., 2013)
This book bridges the technology and business aspects of thermoplastics, providing a guide designed for engineers working in real-world industrial settings. The author explores the criteria for material selection, provides a detailed guide to each family of thermoplastics, and also explains the various processing options for each material type. More than 30 families of thermoplastics are described with information on their advantages and drawbacks, special grades, prices, transformation processes, applications, thermal behaviour, technological properties (tenacit.